الدرس المعجمي العربي لدى اللغويين الأقدمين في ضوء اللسانيات الحديثة - Zulkipli Md Isa; Nurhasma Muhamad Saad; Sulaiman Ismail; Wan Moharani Mohammad; Muhammad Marwan Ismail; Yuslina Mohamed (Penerbit Universiti Sultan Zainal Abidin, 2024)
Vol. 1 No. 1